2017
DOI: 10.1080/15538362.2017.1381873
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antioxidant Content and Capacity in Yellow European Plums

Abstract: Phenolic content and antioxidant capacity of five Yellow European plums (Prunus domestica) were studied using heat reflux extraction. Fresh plums were extracted at 50°C and 70°C, while freeze dried plums were extracted at 50°C, 60°C, and 70°C. Quantification of phenolic compounds such as ascorbic acid, neochlorogenic acid, and chlorogenic acid, was performed using high performance liquid chromatography. Antioxidant activity was determined by evaluating the scavenging ability of 2,2-diphenyl-1-picrylhydrazyl (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 36 publications
7
14
0
1
Order By: Relevance
“…All genotypes were found to contain a high concentration of neochlorogenic acid, followed by chlorogenic acid, and ascorbic acid. This is consistent with other studies that have reported neochlorogenic acid to be the predominant compound found in plums and other stone fruits …”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…All genotypes were found to contain a high concentration of neochlorogenic acid, followed by chlorogenic acid, and ascorbic acid. This is consistent with other studies that have reported neochlorogenic acid to be the predominant compound found in plums and other stone fruits …”
Section: Resultssupporting
confidence: 94%
“…Also, V97261, in comparison to other genotypes studied, yielded the lowest scavenging activity. This observation was also reported by DiNardo et al, who stated that V97261 yielded the lowest scavenging activity among all other genotypes due to its large size.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations